Agile transformation: a multi-dimensional process - Gandomani, Taghi Javdani; Zulzalil, Hazura; Nafchi, Mina Ziaei (Penerbit UTM Press, 2015)
Software companies are widely interested to use Agile methodologies instead of traditional methods, mainly because of achieving the values offered by Agile approach. However, literature review implies that the alteration process is subject to various serious challenges that make Agile transformation more difficult than expected. Most of the companies are facing these challenges mainly because of the lack of knowledge and understanding of the transformation process. We have conducted a large-scale empirical research study discover various aspects of Agile transformation. Applying a Grounded Theory study identified the general outline of Agile transformation Process. The main aim of this paper is to illustrate the most important concepts that need to be considered when adopting Agile methodologies. This study showed that Agile transformation comprises many concepts, activities, and steps including transformation prerequisites, facilitators, framework, assessment, coaching, and so on. Software companies and organizations need to be familiar with these concepts before inception of Agile transformation process.